Seed treatment with trichoderma and chemicals to improve physiological and sanitary quality of wheat cultivars1 - Couto, Ana Paula Silva; Pereira, Alana Emanoele [UNESP]; Abati, Julia; Fontanela, Maira Laíza Camargo; Dias-Arieira, Claudia Regina; Krohn, Nádia Graciele (FapUNIFESP (SciELO), 2021)
– Seed treatment with fungi of the genus Trichoderma spp. provides several benefits, including plant growth promotion, stress tolerance, and pathogenic fungi control. Moreover, to avoid inadequate doses and unnecessary costs, these treatments must be applied in proper amounts. However, no study has evaluated their applicability in wheat seeds. This study aimed to determine the most efficient dose of Trichoderma-based products applied as a seed treatment for improving the physiological and sanitary quality of the wheat cultivars TBIO ‘Toruk’ and TBIO ‘Sossego’, besides comparing the performance of biological and chemical agents. Two biological treatments (Trichoderma asperellum SF 04 and Trichoderma harzianum IBLF006) were applied at 0 (control), 5 × 1011, 1 × 1012, 1.5 × 1012, and 2 × 1012 colony-forming units (CFU) 100 kg−1 seed. Two chemical treatments (carboxin + thiram and pyraclostrobin + thiophanate-methyl + fipronil) were applied at the manufacturers’ recommended doses. Seed germination, shoot and root lengths, seedling dry matter, and sanitary quality were analyzed under laboratory conditions, while seedling emergence, shoot length, and shoot dry matter were analyzed under greenhouse conditions. The optimal dose for wheat seed treatment with T. asperellum SF 04 and T. harzianum IBLF006 was 2 × 1012 CFU 100 kg−1 seed. When comparing biological and chemical products, our findings indicate that both options are adequate for managing wheat diseases and providing seedling growth via seed treatment.
Tratamento de sementes com tricoderma e químicos para melhoria da qualidade fisiológica e sanitária de cultivares de trigo
Keywords: Biological control; Fungicides; Microbiolization; Triticum aestivum